Connections between the distribution of prevailing winds in the winter Northern Hemisphere, solar/geomagnetic activity and the QBO phase - Bochníček, J.; Hejda, P. (Studia Geophysica et Geodaetica)
The effect of solar/geomagnetic activity and QBO phase on the distribution of winds prevailing in the winter periods (January–March) in the Northern Hemisphere at the altitude of 850 mb was studied. Analysis has shown that the zonal flow over the North Atlantic under high geomagnetic activity intensifies and under low solar/geomagnetic activity weakens. Flow deviations, associated with geomagnetic activity, are more marked under the QBO-east phase, and flow deviations, associated with solar activity, are more marked under the QBO-west phase. The results reported by Venne and Dartt (1990) concerning the wind distribution in the winter (February–March) Northern Hemisphere under high and low solar activity and a QBO-west phase, have been confirmed, and supplemented with wind distributions under high and low geomagnetic activity.